PENGARUH BAHAN ORGANIK TERHADAP DAYA IKAT AIR PADA TANAH ULTISOL LAHAN KERING - Nikodemus Dongga Panda; Uska Peku Jawang; Lusia Danga Lewu (Departemen Tanah, Fakultas Pertanian, Universitas Brawijaya, 2021)
Ultisol is one of the soils with limited physical characteristics. The water content is low, the permeability is not enough to pass water into the soil, and the organic-C content is classified as moderate. So that it affects the soil in storing low water, one solution to overcome the physical characteristics of is to provide organic matter into the soil. The purpose of this study was to determine the physical characteristics of Ultisol and to determine the effect of the combination of organic matter from cow dung and rice husk ash on the soil water holding capacity of ultisols on dry land. This study was conducted at the Laboratory of Wira Wacana Christian University, Sumba. This study used a completely randomized design with six treatments and four replications. Observation data were subjected to analysis of variance followed by LSD advanced test with a confidence level of 5%. The results showed that the application of organic matter on the soil significantly affected water content, field capacity, permeability, and C-organic. The application of organic matter can improve soil structure, not soil texture gave a very significant effect, and the treatment that had the best water content was 75% cow dung + 25% rice husk ash.